Macro and microscopic structure of parotids salivary glands in two species of procyonidae: raccoon (Procyon cancrivorus, G. Cuvier, 1798) and coati (Nasua nasua, Linnaeus, 1766) - Celina Almeida Furlanetto Mançanares (Biotemas, 2012)
Coati (Nasua nasua), a diurnal animal, and raccoon (Procyon cancrivorus), a crepuscular and nocturnal one, are species of terrestrial mammals, belonging to the procyonidae family, that are widely found in the Brazilian territory. For this work were used three adult coatis and two adult raccoons adults from the Scientific Breeding-Cecrimpas of Centro Universitario da Fundacão de Ensino Octávio Bastos (Ibama 02027.003731/04-76) were used, from which tissue samples of parotid salivary glands were obtained and stained H.E. for light microscopy. It was found that the parotid glands of coatis and raccoons has a positioning similar to that of the other domestic carnivores, opening their ducts within the oral cavity close to the fourth upper premolar tooth, as well as that histologically the parotid glands of coatis and raccoons are formed by serous acini, similarly to most of the domestic animals, humans beings and rodents, and differently from the results found in young dogs, lambs and some carnivores such as the ferret which have mixed acini and other ones which have serous. One concludes that the similarity in serous constitution of the parotid glands of coatis and raccoons might be due to the omnivorous feeding habit shared by these two species.